Core competencies for Registered Nurse preceptors: A mapping review of quantitative studies - Colleen L. Ryan; Robyn Cant; Lynda Hughes; Darrelle Ahchay; Karen Strickland (Wiley, 2024)
Abstract Aims To review the contemporary international literature on nurse preceptor competencies and map the components and their descriptors. Review Methods A mapping review. Data Sources Articles reporting evidence‐based and validated Registered Nurse (RN) preceptor competencies published between 2013 and 2022 were identified. Open access databases such as PubMed and Google Scholar and the library healthcare databases Scopus and CINAHL were searched. The authors collaborated at each review stage that included screening, article selection, tabulation, mapping and preparation of findings. Results Seven quantitative studies were included. Three were based on existing nurse preceptor competency data sets and four were purposely developed using collaborative research methods. Each study validated findings through a survey of nurse stakeholders. Three key competencies shared across all studies were 'facilitating teaching', 'being a role model' and 'evaluating student's performance'. The number of competency categories ranged from three to 10 and the accompanying item descriptors from 9 to 83. Although terminology describing data sets was inconsistent, similarity was seen across competency domains. Conclusion The contemporary nursing preceptor role is considered an emerging specialist education role. The results offer a set of validated preceptor competency descriptors, applicable to practice, that provide insight into ways employers may recruit, support and retain nurse preceptors. Implications for the Profession The mapped results provide a concise summary of nurse preceptor competency research internationally that can inform further development of RN preceptors. Impact This review addresses the lack of consensus around nursing preceptor competencies for clinical supervision of undergraduate nursing students. Seven competency domains were identified describing key preceptor role capabilities. The domains Facilitator', 'Role model' and 'Evaluator' featured across the included studies: 'More than 300 competency descriptors were reported'. Our review results could better prepare RN preceptors for their important role. Employers of RN preceptors could use the results to design performance competencies that may enhance nursing preceptorship. Reporting Method This review adheres to the PRISMA‐ScR EQUATOR guidelines as the recommended reporting method for mapping reviews.